Quality of Initial Reduction of Tibial Plafond Fractures as Predictors of Trauma Injury Outcome - Jennie-Ann L. Wilson MSc, RRT (Foot & Ankle Orthopaedics)
Category: Ankle; Trauma Introduction/Purpose: High energy trauma to the ankle joint can cause soft tissue damage and bone disruption of the tibial plafond. Currently, the most widely accepted treatment options are the External Fixation and the Open Reduction and Internal Fixation (ORIF) surgical procedures. The goal of this study was to determine if the quality of these procedures in patients with a Type-C Tibial Plafond Fracture has a relationship with a patient’s chances of developing a post-surgical complication. Methods: This retrospective study included a population of 131 patients with a Type-C Tibial Plafond Fracture who were operated on at Grady Memorial Hospital from 2012 to 2023. No exclusions based on past medical history were applied. Grady Sectra Fluoroscopy videos as well as AP and Lateral x-rays were evaluated and the AP translation, Lateral Translation, Anatomic Lateral Distal Tibia Angle (aLDTA), and Anterior Distal Tibia Angle (ADTA) measurements of the tibial plafond fracture post External Fixation and ORIF procedures were recorded, and any differences were assessed. Binary Logistic Regression was used to determine if there was a significant difference in any of the External Fixation measurements and post-operative complications. Pearson Correlation was used to determine if the alignment in the External Fixation was a predictor of the alignment after ORIF. Results: The initial population sample of 131 patients was reduced to 99 patients due to patients being excluded from the study because their imaging files were incomplete. The data showed that neither the translational nor angular alignments post External Fixation nor ORIF had any statistically significant correlation to a patient’s chances of developing a post-surgical complication. Using the Pearson Efficient, the External Fixation AP and Lateral translation measurements were 0.16 (p-value 0.12) and 0.171 (p-value 0.095) respectively, so there was no significant correlation to the final AP and Lateral measurements of the ORIF procedure. The External Fixation aLDTA and ADTA values of 0.289 (p-value 0.004) and 0.336 (p-value < 0.001) respectively, were significantly related to the final aLDTA and ADTA angles of the ORIF procedure. Conclusion: The results from this study will have a positive implication on clinical practice as it encourages trauma orthopedic surgeons to achieve tibial plafond alignment angles during the External Fixation procedure that are as anatomically correct as possible in order to improve the efficacy and accuracy of the ORIF procedure.